Effect the Local Fly Ash on Cement Mortar Properties (Journal of University of Babylon for Engineering Sciences, 2018)
It is good to disposal the byproducts of bricks factories because of pollution of the environment. But the big challenge is to use these byproducts while imposing the properties of construction material and keeping pace with materials technology progress. So, in this study a byproduct (fly ash) of Al Aslaah bricks factories in the south Iraq is used to evaluate the effects for physical properties of the Portland cement mortar. Mortar cubes of 7cm were cast with fly ash partial replacement of cement weight (5%, 10%,15% and 20%) and compared against standard cement mortars cubes. The investigations involved the compressive strength, setting time, heat of hydration and density. While the results illustrate that the increasing of fly ash replacement percentage has significant increase in initial and final setting time and reduces the early and peak temperature of hydration. Also the density got proportionally less values with increasing the fay ash replacement. However, at early ages, 3days the compressive strength values were declined for all the fly ash percentages, but the situation changed for percentage 5% and 10% fly ash replacement at later age and the compressive strength were passed the standard cement mortar values at age 28days.